The Effectiveness of Using Think Pair and Share Technique on Students’ English-Speaking Performance - Apriliani, Meisya Alfiolin; Purnamasari, Asri (JET (Journal of English Teaching), 2024)
Speaking is very crucial for English as a Foreign Language (EFL) learners. However, many students find it challenging to master due to the use of improper teaching and learning approaches. Research suggests that one teaching method that can effectively help to solve the problem is a strategy of the collaborative learning approach called Think Pair and Share (TPS). This study aimed to determine the effectiveness of using TPS on English-speaking skills for students at SMPN 117 Jakarta. Using a quasi-experimental design, this study involved 72 eleventh graders who were divided equally into the control group and the experimental group. Data was collected using pre-tests and post-tests and analyzed using SPSS version 26. The results showed there was a significant effect of using TPS on students' English-speaking performance but no significant difference between the speaking scores of male and female students, indicating that both male and female students benefit equally from TPS use. Based on the results, EFL teachers are recommended to implement this technique to help students develop their speaking performance.